Stability of hybrid stochastic differential systems with switching and time delay. Issue 3 (4th May 2017) - Pu, Xing-cheng; Tan, Xue-gang
ABSTRACT: This article introduces a hybrid stochastic differential system with impulsive, switching and time-delay. Some stability criteria of p -moment global asymptotical stability, p -moment global exponential stability and mean square stability of this system are derived by using switching Lyapunov function approach, Itô formula, impulsive differential inequality method, and linear matrix equality techniques. Three examples are presented to demonstrate the efficiency of the obtained results.